Faktor Yang Mempengaruhi Praktik Transfer Pricing Pada Perusahaan Non-Cyclical Yang Terdaftar Di BEI - Jihanda, Cannaviero; Sufiyati, Sufiyati (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to determine and analyze the effect of profitability, leverage, tax avoidance, tunneling incentives, and bonus mechanisms on transfer pricing in non-cyclical companies listed on the Bursa Efek Indonesia in the 2019-2021 period. The sampling technique uses purposive sampling in the form of secondary data taken from www.idx.co.id or the company's official website. The number of samples in this study were 39 samples. The data analysis method used is descriptive statistics, classical assumption test, and multiple linear regression analysis using the SPSS (Statistical Package for Social Science) application. The results of the study show that leverage has a negative effect on transfer pricing. This research is expected to provide insights that influence transfer pricing practices in Indonesia